2004
DOI: 10.1111/j.1523-1755.2004.00803.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of abundant calcium phosphatein routinely analyzed kidney stones

Abstract: Stone CaP% has risen for three decades. CaP SF, particularly with brushite stones, receive more ESWL treatments than CaOx SF, not explained by stone number or duration of stone disease. Urine supersaturations explain the high CaP%. High CaP% does not hamper medical stone prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
3
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(164 citation statements)
references
References 37 publications
3
156
3
2
Order By: Relevance
“…Some studies have shown that CaOx stones may transform into CaP stones over time, and use of citrate therapy may explain this phenomenon. 50,51 However, no definitive studies have yet proved or refuted the role of citrate in transformation of CaOx to CaP stone disease.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that CaOx stones may transform into CaP stones over time, and use of citrate therapy may explain this phenomenon. 50,51 However, no definitive studies have yet proved or refuted the role of citrate in transformation of CaOx to CaP stone disease.…”
Section: Discussionmentioning
confidence: 99%
“…Urine pH rises progressively with increasing CaP percentage in stones (93). The mechanism of increased urinary pH in CaP SFs is unknown.…”
Section: High Urine Ph As a Main Risk Factor For Cap Stonesmentioning
confidence: 99%
“…Some data suggest that calcium phosphate stones have increased in prevalence. If true, the reasons are uncertain and have been attributed to treatment with citrate supplements (see below) or adverse effects of extracorporeal shockwave lithotripsy (3,4). Lithotripsy has been hypothesized to lead to defective urinary acidification, but this effect is highly speculative.…”
Section: Overview Of Calcium Phosphate Stonesmentioning
confidence: 99%